Access to life-saving medical resources for African countries: COVID-19 testing and response, ethics, and politics (2020)
Coronavirus disease 2019 (COVID-19) has revealed how strikingly unprepared the world is for a pandemic and how easily viruses spread in our interconnected world. A governance crisis is unfolding alongside the pandemic as health officials around the world compete for access to scarce medical supplies. As governments of African countries, and those in low-income and middle-income countries around the world, seek to avoid potentially catastrophic epidemics and learn from what has worked in other countries, testing and other medical resources are of concern. With accelerating spread, funding is urgently needed. Yet even where there is enough money, many African health authorities are unable to obtain the supplies needed as geopolitically powerful countries mobilise economic, political, and strategic power to procure stocks for their populations.